LITERATUR REVIEW : POLA ASUH ORANG TUA UNTUK MENUNJANG PERKEMBANGAN ANAK TERHADAP IDENTITAS REMAJA - Rahmayanty, Dinny; Pebrianto, Agung; Waroh, Mona; Putriansyah, Eliza; Yollanda, Yollanda (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Teenagers are figures who are in a state of high curiosity and are in the phase of searching for their identity. Parents have an important role in how teenagers find their identity and independence. The aim of this literature insight is to understand parenting models to support adolescent identity formation. The results of the literature view show that the parental model that optimizes teenagers' identity is authoritative parenting, patient parenting, parents are considered more democratic in communicating, giving teenagers independence in thinking and acting and investing in things that include their lives and those of the younger generation. as a family education center. The method used in writing this article is Review literature by collecting several journals as sources. The formation of identity and independence is not an individual process but a joint and interdependent process in which adolescents and parents take part. Different parenting styles have different roles in forming a teenager's identity.